Transabdominal preperitoneal laparoscopic hernia repair in treatment of incarcerated inguinal hernia - YANG Lianggen, ZHU Junqiang, HU Xingchen (Waike lilun yu shijian, 2022)
Objective: To evaluate the clinical effect of transabdominal preperitoneal laparoscopic hernia repair in the treatment of incarcerated inguinal hernia. Methods: Retrospective analysis was done with the clinical data of 44 patients of incarcerated inguinal hernia enrolled and operated in our hospital from January 2015 to December 2019. Twenty-four cases in study group were treated with transabdominal preperitoneal laparoscopic hernia repair and 20 cases undergoing Lichtenstein surgery in control group. Operative time, the time of first postoperative off-bed activities, postoperative hospital stay, pain score of first postoperative day, total hospital cost were compared between two groups. Follow-up was done for 12 months and postoperative seroma, incision infection, mesh infection, and recurrence were compared between two groups. Results: Operative time and total hospital cost in study group were higher than those in control group，(80.96±13.25) min vs. (64.90±18.80) min (P<0.05), (16 389.07±2 034.72) yuan vs. (12 516.52±2 545.90) yuan (P<0.05). However, the time of first off-bed activity after operation and postoperative hospital stay were shorter in study group than those in control group, (8.42±3.60) h vs. (11.00±3.52) h (P<0.05), (3.88±0.90) d vs. (4.80±1.32) d (P<0.05). Pain score of first day was lower in study group than in control group (2.25±0.74) vs. (2.80±0.70) (P<0.05). There were no significant differences in postoperative seroma, incision infection between study group and control group(P>0.05). Conclusions: Transabdominal preperitoneal laparoscopic hernia repair in the treatment of incarcerated inguinal hernia had longer operative time and higher cost, but with the advantages of less pain and faster recovery after surgery.